Spin structure and magnetic frustration in multiferroic RMn2O5 (R = Tb, Ho, Dy) - Blake, G; Chapon, L; Radaelli, P; Park, S; Hur, N; Cheong, S; Rodriguez-Carvajal, J (2005)
We have studied the crystal and magnetic structures of the magnetoelectric materials RMn2O5 (R = Tb, Ho, Dy) using neutron diffraction as a function of temperature. All three materials display incommensurate antiferromagnetic ordering below 40 K, becoming commensurate on further cooling. For R = Tb, Ho, a commensurate-incommensurate transition takes place at low temperatures. The commensurate magnetic structures have been solved and are discussed in terms of competing exchange interactions. The spin configuration within the ab plane is essentially the same for each system, and the radius of R determines the sign of the magnetic exchange between adjacent planes. The inherent magnetic frustration in these materials is lifted by a small lattice distortion, primarily involving shifts of the Mn3+ cations and giving rise to a canted antiferroelectric phase.